Designing an index for assessing wind energy potential - Matthias Ritter; Zhiwei Shen; Brenda López Cabrera; Martin Odening; Lars Deckert (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
To meet the increasing global demand for renewable energy such as wind energy, more and more new wind parks are installed worldwide. Finding a suitable location, however, requires a detailed and often costly analysis of the local wind conditions. Plain average wind speed maps cannot provide a precise forecast of wind power because of the non-linear relationship between wind speed and production. In this paper, we suggest a new approach of assessing the local wind energy potential: Meteorological reanalysis data are applied to obtain long-term low-scale wind speed data at turbine location and hub height; then, with actual high-frequency production data, the relation between wind data and energy production is determined via a five parameter logistic function. The resulting wind energy index allows for a turbine-specific estimation of the expected wind power at an unobserved location. A map of wind power potential for whole Germany exemplifies the approach.
Keywords: Q42; Q47; 330; Wind power; energy production; renewable energy; onshore wind; MERRA